Investigation of Optical Multi Input Multi Output (OMIMO) transmission link using Multimode Fiber - Prasad, Prashuram (My University, 2013)
Optical fibers are an integral part of current networking architectures due to their ability to support extremely high data rate. The rapid growth of bandwidth requirement due to the exponential increase in end-user’s bandwidth imposes new challenges to the short and medium distance networks. Theoretically the multimode fibers (MMF) exhibit a higher transport capacity limit than single mode fibers (SMF) by exploiting the various modes or groups of modes as independent communication channels with individual scattering paths. Multiple optical sources and detectors are introduced to take advantage of the spatial (modal) diversity, it is possible to recover signal transmitted using multiple transmitter over a single MMF, at the expense of greater signal processing complexity, particularly at the receiver end. The single-mode fibers (SMFs) provides high speed and long-distance optical links. However, these improvements also come with additional complexity in transmitter, receiver, alignment and packaging, thus making them costly and inappropriate for small and medium sized networks In this thesis work we have proposed a MIMO MMF link which utilizes the transmitter and receiver diversity with spatial diversity offered by MMF, which help in improving the system performance. The modes propagating inside the MMF are used in constructing way. The 3x3 and 5x5 MIMO systems are proposed to improve the reliability of transmitted bits. The effect of changing the data rate is also observed. The linearly polarized modes are used to achieve higher data and capacity from MMF. The maximum optical transmission range is also calculated with the help of proposed system design. The power coupling between the propagating modes and bending of MMF are investigated; the system performance is analyzed with the help of BER, received optical power, Q factor and eye diagrams. The measured result shows that MMF has great capability to support higher data and high capacity to a longer distance. i
ME, ECED
Keywords: MIMO; Optical; MMF; BER